Evaluation of Local Health Fund Performance in the Area of Three Southernmost Provinces - สารีมาแซ, อิบรอฮิม; ไกรวาส, กิจฐเชต; ปิ่นตบแต่ง, ประภาส (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
This piece of research is aiming to evaluate the performance of the local health fund in the three southernmost provinces. Samples 159 executive committees of the local health fund in Pattani, Yala, and Narathiwat by districts stratified sampling and determinate the sample size from the population rate of each province. The research tool is a set of qualified questionnaire survey where Cronbach's alpha coefficient. The Cronbach's alpha coefficient in the questionnaire of the executive committee of the local health fund was equal to 0.98, The statistics used in the analysis were percentage, mean, and standard deviation. The study found that to achieve the goals of the local health fund in the three southernmost provinces, at ( = 4.04). In-depth study found that they have high attitude toward the administration at (= 4.12), the strategy planning at ( = 4.08), the monitoring and evaluation at ( = 4.05), the management at ( = 4.04), the congruity of the local health fund committee at (= 4.03), the budget at ( = 4.00), and the material at ( = 3.97). On the other hand, the attitudes toward the performance of the local health fund in the three southernmost provinces were overall at the high level at (= 4.12). In-depth study found that the highest rate was the government’s regulations and policies at (= 4.24) and following by the staffs at (= 4.15), the budget at (= 4.11), the form of performance at (= 4.09), and the collaboration procedure and the development format at (= 4.03).